Mining investment scenario. Quellaveco Project - Moquegua - Zavaleta López, Ciro Alejandro (2011)
The implementation phase of the plant and commencement of operations of the copper deposit Quellaveco 2015 has entered a relatively critical stage , because , should get the social license. An opponent citizen sector linked to the agricultural sector represented by the board of users Irrigation District Moquegua and leaders of the Front for the Defense of Moquegua and City Council District Torata question the environmental impact study and activities implemented by the company in the area where the site is located. The Regional Government has constituted a roundtable this year with participation of the National Government , Local Government , Civil Society and Mining Company , meetings leading to the making of a political and technical decision to fully resolve this project in terms of development and improvement in the quality of life of the population. On the other hand, the absence of the University in terms of its linked to the set (system) of the mining operation would bring in better targeting of knowledge , experience, research and transparency of these investment professionals is appreciated.